2011
DOI: 10.1097/scs.0b013e31822e5cf8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Lipofilling and a Nonabsorbable Filler for Facial Wasting Rehabilitation in HIV-Positive Patients

Abstract: We can treat HIV-related lipodistrophy more extensively with lipofilling because, after harvesting the fat graft, other body contouring procedures also can be performed; there is a better aesthetic outcome in facial rehabilitation performed with lipofilling, probably due to the possibility to fill deeper than with nonabsorbable fillers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
(13 reference statements)
0
15
0
Order By: Relevance
“…Lipofilling significantly improved facial esthetics, but evaluation at 48 weeks found that facial volume had decreased to baseline levels in all but one patient . However, as Rauso et al . later noted in 2011, the study by Negredo et al .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Lipofilling significantly improved facial esthetics, but evaluation at 48 weeks found that facial volume had decreased to baseline levels in all but one patient . However, as Rauso et al . later noted in 2011, the study by Negredo et al .…”
Section: Resultsmentioning
confidence: 87%
“…These included one RCT and eight observational 15 Lipofilling significantly improved facial esthetics, but evaluation at 48 weeks found that facial volume had decreased to baseline levels in all but one patient. 15 However, as Rauso et al 43 later noted in 2011, the study by Negredo et al 15 does not report on whether or not overfilling was performed. Overfilling is a technique used to overcorrect the defect in facial volume because studies have shown that some of the transferred fat will be lost.…”
Section: Silicone Oilmentioning
confidence: 99%
“…Lipofilling resulted in a better aesthetic outcome than PAAG in injections, especially by the ability to inject the autologous fat deeper than the synthetic filler. 135 Another study by Uzzan et al . showed similar results.…”
Section: Therapymentioning
confidence: 98%
“…134 However, recent studies have shown success with lipofilling for facial wasting. 135,136 In a clinical prospective study 23 HIV-infected patients suffering from FLA were treated either with lipofilling (14 patients) or with PAAG (9 patients). 135 Fat was harvested from lipohypertrophied areas such as the lower abdomen, mammary region and buffalo hump.…”
Section: Therapymentioning
confidence: 99%
“…A prospective study assessed 23 HIV-positive patients with facial lipoatrophy who were randomized to undergo treatment with autologous fat transfer or Aquamid. 13 Follow-up visits were scheduled at 3, 6, and 12 months after initial evaluation to evaluate clinical efficacy. The primary endpoint in the study used the Global Aesthetic Improvement Scale, which was measured by the investigator 1 year after baseline.…”
Section: Clinical Efficacy Of Aquamidmentioning
confidence: 99%